2017
DOI: 10.1038/srep45979
|View full text |Cite
|
Sign up to set email alerts
|

SERS spectral study of HAuCl4-cysteine nanocatalytic reaction and its application for detection of heparin sodium with label-free VB4r molecular probe

Abstract: In the presence of nanocatalyst, L-cysteine reduce HAuCl4 rapidly to form gold nanoparticles (AuNP), and a quick nanocatalytic preparation procedure was established for Au/AuNP sol with highly active surface enhanced Raman scattering (SERS) effect and good stability. The nanoreaction was also studied by absorption, resonance Rayleigh scattering (RRS), transmission electron microscopy (TEM) and energy spectra. In the selected conditions, the analyte heparin sodium (HS) could react with victoria blue 4 R (VB4r) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Considering AgNPs are easily oxidized and less stable than AuNPs, AuNP-based platforms were chosen as the target products. 20 Besides, it is reported that dielectric materials can localize electric fields by multiple scattering of light. 21 When AuNPs are assembled with dielectric materials, surface plasmon of AuNPs and their electric dipoles are simultaneously generated upon exposure to light.…”
Section: Introductionmentioning
confidence: 99%
“…Considering AgNPs are easily oxidized and less stable than AuNPs, AuNP-based platforms were chosen as the target products. 20 Besides, it is reported that dielectric materials can localize electric fields by multiple scattering of light. 21 When AuNPs are assembled with dielectric materials, surface plasmon of AuNPs and their electric dipoles are simultaneously generated upon exposure to light.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has looked into the development of novel detection methods coupled with nanozymes. 50,51 In this study, an immunosensor was developed using silver nanoparticles as the nanozyme instead of the biological enzyme using a simple one-step synthesis of silver nanoparticles deposition. Gold nanoparticles were used as the seed platform and to enhance the sensitivity of the sensor by increasing the surface area for seeding of silver nanoparticles, as well as for the conjugation of detecting antibodies, which will result in a higher likelihood of detecting the target protein.…”
Section: Introductionmentioning
confidence: 99%
“…16 Generally, SERS signal depends upon a number of factors. However, the substrateadsorbed molecular probe can greatly amplify the signals and it is linear to the SERS signal at some certain conditions, 17,18 and an SERS method can be developed for the detection of the molecular probe. Javier and Ronei 17 studied a paper-based portable SERS method for the detection of uric acid, with an LR of 0-3.5 mmol/L and a DL of 0.11 mmol/L.…”
Section: Introductionmentioning
confidence: 99%
“…Javier and Ronei 17 studied a paper-based portable SERS method for the detection of uric acid, with an LR of 0-3.5 mmol/L and a DL of 0.11 mmol/L. Wang et al 18 used the catalytic activity of GO to catalyze the H 2 O 2 -HAuCl 4 system, and then ligands regulated the use of SERS to detect human chorionic gonadotropin, and Hg 2+ in concentrations ranging from 0.25 to 10 ng/mL, 0.25-10 nmol/L, was tested on samples which showed good recovery. Frost et al 19 developed a SERS sensor based on citrate-functionalized AuNP for 50-1,000 ng/L Pb 2+ .…”
Section: Introductionmentioning
confidence: 99%